Review of La alquimia de la bestia - Vargas Mena, Emilio (2024)
This is a review of the novel written by Luis Diego Guillén, La alquimia de la bestia (The Beast’s Alchemy), winner of the National Prize of Literature in 2016, edited by URUK editors in San José, Costa Rica,in the same year. The novel consists of 512 pages and has the ISBN 978-9930-526-22-4.